Analisis Kelayakan Usaha Kerupuk Udang Di Kecamatan Sukadana Kabupaten Kayong Utara - Merry Andari Syahputri; Didik; Tohari, Sabda Agung Imam (Jurnal Riset Ilmu Pertanian dan Ekonomi, 2025)
This research aims to analyze the feasibility of the mackerel amplang business in Teluk Batang District, North Kayong Regency. This type of research is quantitative. Respondent data was collected using questionnaires, interviews, observation and documentation. The research location was chosen deliberately, namely in Teluk Batang District, North Kayong Regency. The sample for this research was 2 mackerel fish entrepreneurs. The sampling technique uses a purposive sampling technique (intentionally). This research uses income analysis to find costs and revenues. This research also uses financial analysis with the criteria of Net Present Value (NPV), Benefit Cost Ratio (B/C), Internal Rate of Return (IRR) and Payback Period (PP). The results of the research show that the mackerel fish amplang business in Teluk Batang District, North Kayong Regency is worth pursuing with data analysis of the NPV of Amanda amplang of IDR 85.984.000 and Deby amplang of IDR 155.601.514, the IRR of Amanda amplang is 0,47% and Deby amplang of IRR is 0,55. The B/C Ratio in Amplang Amanda’s research is 5,61 and the B/C Ratio of Amplang Deby is 11,85 and the Payback Period of Amplang Amanda is 1,37 and the Payback Period of Ampang Deby is 1,22. So it takes 5 years to return the investment capital.